Initial GCS and laboratory findings of patients with TBI are associated with the GOSE and mortality rate at one year - Paydar, Shahram; Bordbar, Elahe; Taghipour, Mehdi; Khalili, Hosseinali; Jafari, Mehran (International Journal of Research in Medical Sciences, 2017)
Background: To evaluate the relationship between presenting Glasgow Coma Scale (GCS) or laboratory data of patients with TBI and Extended Glasgow Outcome Scale (GOSE) and final outcome (deceased, survived) at one year. Methods: 74 patients (59 males and 15 females; mean age ±SD of 40±19years) who presented with TBI were entered into the study, and their GCS and laboratory data were recorded. After one year, GOSE level and final outcome were evaluated with 11 yes/no questions obtained from the patients or their first-degree relatives. Results: The patients with lower GCS on admission or day six, significantly had lower GOSE. Moreover, the lower the GCS in the first week of admission, the poorer the final outcome. Among laboratory data, the base deficit (BD) level of -6 or worse on admission was an indicator of mortality at one year. Hypernatremia was the only laboratory factor which predicted poor GOSE after a year. Furthermore, patients with serum hypernatremia, hyperkalemia, or high PTT levels on the first week of admission had poor final outcome. Conclusions: Presenting GCS and metabolic derangements are reliable indicators of long-term outcome and GOSE at one year.